A Study of Retailers’ Awareness of Goods and Services Tax (GST) - Rajnish Sharma (Innovative Research Thoughts, 2022)
The present study was carried out to know the level of awareness of retailers about goods and services tax. Goods and Services Tax (GST) is a structure of indirect taxes formulated to increase the growth of the country. In other words, it is a simplification over Indian taxation system. Through this simplification, Indian government aims to increase the level of revenue, provide easy way to paying-tax and file return by the businessmen and to protect the tax evasion and tax avoidance. Besides this, in India, government had started reforms for indirect taxes with the replacement of sales taxes by value added tax (VAT) in 2005. However, in this old taxation system the people of country had to bear cascading effect of taxes- an item was taxed more than once. To get the solution of problems relating to taxation structure government of India implemented the GST on 1st April, 2017. GST was implemented at two stages, first was levied by Central government and called Central Goods and Services Tax (CGST) and second was levied by State govt. and called State Goods and Services Tax (SGST). Under this research work, primary data were collected through a structured questionnaire. Collected data were analysed with the help of percentage analysis.